High-Performance Work Systems and Job Control - Jensen, Jaclyn M.; Patel, Pankaj C.; Messersmith, Jake G. (Journal of Management, 2013)
This study examines relationships among high-performance work systems (HPWS), job control, employee anxiety, role overload, and turnover intentions. Building on theory that challenges the rhetoric versus reality of HPWS, the authors explore a potential “dark side” of HPWS that suggests that HPWS, which are aimed at creating a competitive advantage for organizations, do so at the expense of workers, thus resulting in negative consequences for individual employees. However, the authors argue that these consequences may be tempered when HPWS are also implemented with a sufficient amount of job control, or discretion given to employees in determining how to implement job responsibilities. The authors draw on job demands–control theory and the stress literatures to hypothesize moderated-mediation relationships relating the interaction of HPWS utilization and job control to anxiety and role overload, with subsequent effects on turnover intentions. The authors examine these relationships in a multilevel sample of 1,592 government workers nested in 87 departments from the country of Wales. Results support their hypotheses, which highlight several negative consequences when HPWS are implemented with low levels of job control. They discuss their findings in light of the critique in the literature toward the utilization of HPWS in organizations and offer suggestions for future research directions.